2019
DOI: 10.1080/01612840.2019.1631415
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Adaptation and Psychometrics Properties of the Arabic Version of the Positive Thinking Skills Scale

Abstract: Background Identifying depressive cognitions in first-generation Middle Eastern immigrants (FGMEI) can be an important step to prevent the development of clinical depression. Purpose This study focused on the cross-cultural equivalence and psychometric testing of the Arabic version of the Positive Thinking Skills Scale (A-PTSS) among 100 FGMEI. Methods Content/face validity of the measure was conducted. Internal consistency, homogeneity, dimensionality and construct validity were assessed. Results Cronbach's a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The combined effects of low and middle PT and low and middle AV effects appear to enhance the EE and IWB relationship. Although research studies have shown that individuals may react more strongly to environmental stimuli when it is consistent with their inherent attainment value [16,60,62,63,[81][82][83][84][85], this would help to explain the important of PT. However, it is possible that what drives the PT relationships is the appropriate level of the PT that gives impetus to higher reactivities.…”
Section: Discussion: Open Innovation From Employee Engagement With Attainment Value and Positive Thinkingmentioning
confidence: 99%
See 2 more Smart Citations
“…The combined effects of low and middle PT and low and middle AV effects appear to enhance the EE and IWB relationship. Although research studies have shown that individuals may react more strongly to environmental stimuli when it is consistent with their inherent attainment value [16,60,62,63,[81][82][83][84][85], this would help to explain the important of PT. However, it is possible that what drives the PT relationships is the appropriate level of the PT that gives impetus to higher reactivities.…”
Section: Discussion: Open Innovation From Employee Engagement With Attainment Value and Positive Thinkingmentioning
confidence: 99%
“…PT is a thought process formed by perception and interpretation to generate attitudes and consciousness for oneself, others, objects or situations. PT is a method for tolerating and encountering problems with the strength to live happily and successfully [59,60]. PT is similar to optimism, whereby a person accepts negative reality with understanding, sees problems or difficulties as things that usually happen and knows how to gain advantages from the positive side of such situations.…”
Section: Relationship Between Pt As a Moderator Of Av And Ee On Iwbmentioning
confidence: 99%
See 1 more Smart Citation
“…The Con rmatory Factor Analysis (CFA) supported the unifactorial structure proposed in the original version (3,29) and in Turkish (28), Arabic (54) and Portuguese (55) adaptations. This nding underscores the reliability and validity of the PTSS, a rming its relevance across various cultural contexts.…”
Section: Discussionmentioning
confidence: 56%
“…Bekhet and Zauszniewski 20 evaluated the properties of PTSS in caregivers of individuals with autism spectrum disorders. Bekhet et al 21 conducted a cross-cultural adaptation and evaluation of the psychometric properties of the PTSS in the Arab population. The three previous studies considered positive thinking a skill that improved mental health and quality of life, consistent with the positive psychology approach.…”
Section: Introductionmentioning
confidence: 99%